The Influence of Profitability, Liquidity, Capital Intensity, Solvency and Company Size on Tax Aggressiveness in Mining Sector Companies Listed on the Indonesian Stock Exchange for the 2015–2019 Period - Muhammad Aditya; Elwisam Elwisam; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
Indonesia is Wrong One country Which own riches source Power the largest natural and human resources in the world with a mining industry material the excavation originate from oil And gas earth, coal, copper, gold, silver, nickel and tin. It is conditions like this that attract entrepreneurs to establishing companies in Indonesia, both local and foreign companies with exists existence company the can give profit for Indonesia in increase income country specifically from sector tax. Matter This is interesting for the author to analyze the influence of profitability, liquidity, capital intensity , solvency And size company to aggressiveness tax on mining sector companies listed on the Indonesian Stock Exchange period 2015-2019. In this research the author used secondary data in get from site www.idx.co.id with amount Population Company Which reaching 49 companies in the mining sector listed on the Stock Exchange Indonesia. This research sample used purposive sampling and was selected of 21 sample companies according to certain criteria. Results of this research showing that profitability, liquidity, capital intensity, solvency and size the company has a significant influence on tax aggressiveness.